The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1460-9568.2007.05715.x
|View full text |Cite
|
Sign up to set email alerts
|

Calpain cleavage of collapsin response mediator proteins in ischemic mouse brain

Abstract: Collapsin response mediator proteins (CRMPs) are important brain-specific proteins with distinct functions in modulating growth cone collapse and axonal guidance during brain development. Our previous studies have shown that calpain cleaves CRMP3 in the adult mouse brain during cerebral ischemia [S.T. Hou et al. (2006) J. Neurosci., 26, 2241-2249]. Here, the expression of all CRMP family members (1-5) was examined in mouse brains that were subjected to middle cerebral artery occlusion. Among the five CRMPs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…PDI A3, Hsc70 and Hsp60 are heat shock proteins involved in cellular repair, recovery and survival [17][18][19][20][21] whereas CRMP-2 performs functions related to neurite outgrowth [17,[22][23][24][25]. The RSA found in the brain extracts could result from contamination of the samples by vascular contents which are unavoidably included in the samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDI A3, Hsc70 and Hsp60 are heat shock proteins involved in cellular repair, recovery and survival [17][18][19][20][21] whereas CRMP-2 performs functions related to neurite outgrowth [17,[22][23][24][25]. The RSA found in the brain extracts could result from contamination of the samples by vascular contents which are unavoidably included in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mechanisms of action temporally of neuroprotectants such as selective cathepsin B and L inhibitors is critical for their effective and eventual therapeutic application, since the pathways in which they are involved may serve different functions at different times after ischemia. Within the initial hours after ischemic injury, the cysteine protease pathways may be destructive, whereas, beyond several hours, but within 24 hours, the pathways set in motion by ischemia (heat shock proteins and CRMP) may participate in recovery of cells that survived the initial period of necrosis and early apoptotic cell death [22][23][24][25]. Early neuroprotection followed by subacute neurorestorative therapies may optimize the effective treatment strategies for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies identified that the cleavage was by calpain (13,(22)(23)(24)(25)(26), a Ca 2ϩ -activated protease that has been heavily linked to neurotoxic signaling (27). The cleavage of CRMP2 by calpain occurs following ischemia (23), neurotrauma (26), excitotoxicity (13), and nerve growth factor deprivation-induced neurite degeneration (24).…”
Section: ؉mentioning
confidence: 99%
“…The cleavage of CRMP2 by calpain occurs following ischemia (23), neurotrauma (26), excitotoxicity (13), and nerve growth factor deprivation-induced neurite degeneration (24). This cleavage is not specific to CRMP2, however, because CRMP1, -3, -4, and -5 also appear to be cleaved by calpain following neurotoxic insult (23,26,28). In the present study, we demonstrate that a CRMP2 peptide down-regulates dendritic surface expression of NMDARs and protects against neurotoxicity in cell-based assays and in TBI.…”
Section: ؉mentioning
confidence: 99%
“…C57B/6 mice (20 -23 g) were obtained from Charles River and bred locally. Under temporary isofluorane anesthesia, MCAO was induced by the intraluminal insertion of a silicon-coated nylon filament (Re L910 PK5, Doccol Corporation) through the common carotid artery into the internal carotid artery and left in place for 60 min as we previously described (20)(21)(22)(23)(24)(25)(26). Cerebral blood flow (CBF) was monitored by laser Doppler flowmetry using a probe located in the ipsilateral parietal bone (1-2 mm posterior to bregma), and a >90% reduction in CSF was considered to indicate successful occlusion.…”
Section: Methodsmentioning
confidence: 99%